Design of Mathematics Learning Framework Based on the Perspective of the Qur'an - Lubis, Suhaimi Zefri; Mahdalena, Mahdalena; Zulmaulida, Rahmy (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2023)
Abstract:The concept of inspiring, communicative, and interesting learning based on verses of the Qur'an is expected to be able to foster children's joy in learning mathematics. This is literature research that analyzes and describes the design of a mathematical learning framework based on the perspective of the Qur'an. Research data sources consist of references or literature related to mathematics learning from the perspective of the Qur'an, mainly focused on algebraic concepts such as numbers, various numbers, and number operations. In addition, one expert in the interpretation of the Qur'an was involved as a source of data. Data analysis using content analysis techniques. The results showed that in the Qur'an, various mathematical concepts provide an overview of algebra, namely about numbers, various numbers, and number operations. In addition, there are also various learning activities, including the preparation, implementation, and evaluation stages of learning activities.Abstrak:Konsep pembelajaran yang inspiratif, komunikatif dan menarik yang bersumberkan pada ayat-ayat Al-Qur’an diharapkan mampu menumbuhkan rasa suka cita anak-anak terhadap pembelajaran matematika. Penelitian ini merupakan penelitian pustaka yang menganalisis dan mendeskripsikan rancangan kerangka pembelajaran matematika berdasarkan perspektif Al-Qur’an. Sumber data penelitian terdiri dari referensi atau literatur-literatur terkait pembelajaran matematika dalam perspektif Al-Qur’an, terutama difokuskan pada konsep aljabar seperti bilangan, macam-macam bilangan, dan operasi bilangan. Selain itu, satu orang pakar tafsir Al-Qur’an dilibatkan sebagai sumber data. Analisis data menggunakan teknik analisis isi (content analysis). Hasil penelitian menunjukkan di dalam Al-Qur’an terdapat berbagai konsep matematika dan secara jelas memberikan gambaran tentang aljabar yakni mengenai bilangan, macam-macam bilangan, dan operasi bilangan. Selain itu dijumpai juga berbagai kegiatan pembelajaran diantaranya tahap persiapan, pelaksanaan, dan evaluasi kegiatan pembelajaran.